The Key Competencies Development within the Personal and Social Education - Marešová, Hana (Civilia, 2016)
This article deals with the topic of key competences development within the personal and social education at elementary school. The attention is paid to potentially new topic which should be included within the Frame Educational Programme in the Czech Republic as the one of the goals of education policy of Ministry of Education, Youth and Sports - the entrepreneurial education. The experiences with the entrepreneurial education topic at Faculty of Education at Palacky University in Olomouc are described.
Keywords: Key competences; Elementary school pupils; Personal education; Social education; Entrepreneurial education